Pengaruh Model Pengeringan dan Penyimpanan Umbi Benih terhadap Produksi dan Mutu Bawang Merah (Allium ascalonicum L.) di Lahan Pasir - Andika Timur Hari Pradana; Rajiman, Rajiman; Fauziah, Nicky Oktav (Jurnal Agroteknologi (Agronu), 2025)
Shallots is a horticultural commodity that has economic value and is vital for household consumption and other needs. The continuous demand requires the availability of quality stock. This research aimed to determine the effect of drying and storage models of seed bulbs on the yield and quality of red onion seeds in sandy land. The study was conducted in, Dukuh Patihan, Gadingsari Village, Sanden District, Bantul Regency, Special Region of Yogyakarta, from February 2025 to April 2025. This research used a Completely Randomized Block Design with treatments of drying and storage models: sunlight with leaves (SMDD), sunlight without leaves (SMTD), UV plastic with leaves (PUVDD), and UV plastic without leaves (PUVTD). Data analysis used ANOVA (Analysis of Variance); if the variance showed a significant effect, it was followed by the DMRT (Duncan Multiple Range Test) at a 5% level. The results showed that the use of drying and storage techniques had no significant effect on the parameters of plant height, number of leaves, wet bulb weight per clump, productivity, bulb weight, and had a significant difference in the parameters of dry bulb weight per clump, number of bulbs per clump, bulb diameter, and bulb specific weight. The drying and storage technique using sunlight with leaves (SMDD) produced the best results in terms of plant height, number of leaves, productivity, wet bulb weight per clump, and bulb diameter